Ending sexual violence in college : a community-focused approach - Gavin, Joanne H.; Quick, James C.; Gavin, David J. (Johns Hopkins University Press, 2021)
"In this practical guide for higher education professionals who work in student affairs, the authors lay out a community-based model aimed at eliminating sexual misconduct of all kinds on college campuses"--